PENGARUH METODE ROLE PLAYING TERHADAP HASIL BELAJAR IPS PESERT DIDIK KELAS V SEKOLAH DASAR - Clorinda, Agrippina; Sugiyono, Sugiyono; Rosnita, Rosnita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the effect of the role playing method on the social science learning outcomes of students in the fifth grade of east pontianak state elementary scool 04. The method used in this study is an experimental design and nonequevalent control group design research design. The sample of this study was all students in grade V elementaery school in east pontianak 04 wita total of 84 students. Data collection techniques are measure ment techiques. Data collection tools usedare multiple choice tests. Based on results of pre-test were 75,25 and post-test 77,93. After t-test obtained tcount of 1,737 an ttabel (α = 5%, dk = 42 + 40 - 2) of 1,667. The calculation results show that tcount 1,737> ttabel 1,667 thus Ha is accepted. Based on the calculation of the effect size obtained 0,30 which group in the medium catagory is the effect size range .50 medium. That is, learning to use role playing methods to the category of being on students social science learning outcomes. The conclusion of this study is that there is influence ofrole playing method on the social science in grade V students of east pontianak state elementary school 04. Keywords: Influence, Role Playing Method, Learning Outcomes, Social Sciences.